2006
DOI: 10.1001/archsurg.141.9.885
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parathyroidectomy on Bone Fracture Risk in Patients With Primary Hyperparathyroidism

Abstract: Background: Parathyroidectomy may increase bone density in primary hyperparathyroidism (PHPT), but it is unclear whether fracture risk is decreased. Hypothesis: Parathyroidectomy decreases fracture risk. Design: Retrospective cohort study with median follow-up of 6.5 years. Setting: Twelve regional hospitals in California. Patients: One thousand five hundred sixty-nine patients with PHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 24 publications
1
41
0
1
Order By: Relevance
“…Как правило, в течение первых 2-3 лет после успешно проведенной паратиреоидэктомии проис-ходит активное восстановление костного метабо-лизма, существенный прирост МПК (в среднем 5-10% за год) в зависимости от выраженности кост-ных потерь и возраста пациента [19,[87][88][89]. В этот период может не требоваться дополнительного ле-чения, за исключением назначения препаратов кальция и активных метаболитов витамина D.…”
Section: гиперкальциемический кризunclassified
“…Как правило, в течение первых 2-3 лет после успешно проведенной паратиреоидэктомии проис-ходит активное восстановление костного метабо-лизма, существенный прирост МПК (в среднем 5-10% за год) в зависимости от выраженности кост-ных потерь и возраста пациента [19,[87][88][89]. В этот период может не требоваться дополнительного ле-чения, за исключением назначения препаратов кальция и активных метаболитов витамина D.…”
Section: гиперкальциемический кризunclassified
“…A retrospective study of 1569 patients (452 underwent parathyroidectomy versus 1117 were observed) found that parathyroidectomy was independently associated with a decreased fracture risk (hazard ratio, 28 Similarly, a cohort study of 674 patients who underwent parathyroidectomy compared with 2021 age-and sexmatched controls showed that the patients with HPT had an increased relative rate of fracture before surgery (1.8) but that the rate returned to normal (1.0) after surgery. 29 Furthermore, the increased risk of fracture was evident for up to ten years before parathyroidectomy and was independent of serum calcium concentration.…”
Section: Treatmentmentioning
confidence: 99%
“…As PTH levels normalize after parathyroid surgery, brown tumor is expected to improve in size or to completely resolve [8][9][10][11]. In addition, orthopedic intervention can be necessary in case of pathologic fracture or extensive cortical involvement.…”
Section: Discussionmentioning
confidence: 99%